114k views
2 votes
Solve by elimination 3x+3y=0 and -2x-y=0

User HyperX
by
4.5k points

2 Answers

3 votes
Y=0 because you must get like terms in order to start the process of elimination and once you get same terms then you eliminate. And subtract or add the divide by y or x to get your answer. So y=0
Solve by elimination 3x+3y=0 and -2x-y=0-example-1
User Ahmad Khani
by
4.8k points
1 vote

Answer:


x=0,\:y=0

Explanation:


\begin{bmatrix}3x+3y=0\\ -2x-y=0\end{bmatrix}\\\\\mathrm{Multiply\:}3x+3y=0\mathrm{\:by\:}2\:\mathrm{:}\:\\\quad \:6x+6y=0\\\\\mathrm{Multiply\:}-2x-y=0\mathrm{\:by\:}3\:\mathrm{:}\:\\\quad \:-6x-3y=0\\\\\begin{bmatrix}6x+6y=0\\ -6x-3y=0\end{bmatrix}\\\\\\-6x-3y=0\\+\\\underline{6x+6y=0}\\3y=0\\\\\begin{bmatrix}6x+6y=0\\ 3y=0\end{bmatrix}\\\\\mathrm{Solve}\:3y=0\:\mathrm{for}\:y:\quad y=0\\\\\mathrm{For\:}6x+6y=0\mathrm{\:plug\:in\:}y=0


\mathrm{Solve}\:6x+6\cdot \:0=0\:\mathrm{for}\:x:\quad x=0\\\\x=0,\:y=0

Solve by elimination 3x+3y=0 and -2x-y=0-example-1
User Fasfsfgs
by
4.6k points